BERFILSAFAT DAN BERTEOLOGI DI INDONESIA - Paul Budi Kleden (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: This article exposes the importance of doing philosophy and theology in Indonesian context. The reason is that philosophizing and theologizing are not only pure rational activities, but ways of how to contribute significantly in the context of Indonesian society and Church. Furthermore, the article argues that pluralism, poverty, social welfare and the environmental destruction are fundamental problems and questions that philosophy and theology cope with. However, the questions are not only typical Indonesian, but global problems. Consequently, doing philosophy and theology in Indonesian context is not an exclusive activity, rather than taking part at a global and inclusive process.Keywords: philosophize, theological, Indonesia, pluralism, poverty, environment